2017
DOI: 10.1016/j.cell.2017.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Human ILC Precursors Provide a Substrate for Tissue ILC Differentiation

Abstract: Innate lymphoid cells (ILCs) represent innate versions of T helper and cytotoxic T cells that differentiate from committed ILC precursors (ILCPs). How ILCPs give rise to mature tissue-resident ILCs remains unclear. Here, we identify circulating and tissue ILCPs in humans that fail to express the transcription factors and cytokine outputs of mature ILCs but have these signature loci in an epigenetically poised configuration. Human ILCPs robustly generate all ILC subsets in vitro and in vivo. While human ILCPs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
572
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(656 citation statements)
references
References 52 publications
63
572
3
2
Order By: Relevance
“…Murine parabiosis experiments showed that in adults ~95% of ILC2s do not apparently circulate in blood or replenish from blood-borne precursors, although small numbers of ILC precursors were noted in blood (43). Similarly, rare ILC precursors and ILC2s were identified in human blood (62). Most tissue ILC2s are thought to arise from precursors seeded into tissues before birth, and there is a rapid rise of mature ILC2s in lungs and small intestine in the first weeks after birth (39, 44, 45).…”
Section: Discussionmentioning
confidence: 95%
“…Murine parabiosis experiments showed that in adults ~95% of ILC2s do not apparently circulate in blood or replenish from blood-borne precursors, although small numbers of ILC precursors were noted in blood (43). Similarly, rare ILC precursors and ILC2s were identified in human blood (62). Most tissue ILC2s are thought to arise from precursors seeded into tissues before birth, and there is a rapid rise of mature ILC2s in lungs and small intestine in the first weeks after birth (39, 44, 45).…”
Section: Discussionmentioning
confidence: 95%
“…33 However, we demonstrate that human NKp44 1 bona fide ILC3s from secondary lymphoid tissues can develop into functional equivalents of NK cells, and this developmental pathway, which demonstrates many similarities to NK-cell differentiation from stage 3 precursors, 17,18 might provide cytotoxic protection at mucosal barriers.…”
Section: Nkp44mentioning
confidence: 99%
“…Toutefois, il semblerait que chez l'adulte, des précurseurs périphériques existent. En effet, des précurseurs de cellules NK ont été trouvés en dehors de la moelle osseuse chez l'homme comme chez la souris [30] et des précurseurs des ILC3 ont été identifiés dans les amygdales et le sang périphérique [57] chez l'homme [31]. Le rôle des CHILP de la moelle osseuse chez l'adulte reste à définir.…”
Section: Transition Ilc1-ilc2unclassified